Tracing the evolution of polypharmacy and contraindicated drug‒drug interactions in people living with HIV in Belgium - Lopez Delhoulle, Victoria; Destordeur, Li-Cécile; Maes, Nathalie; Fombellida, Karine; El Moussaoui, Majdouline; Darcis, Gilles (Frontiers in Pharmacology, 2025)
BackgroundPeople living with HIV (PWH) are more likely to develop comorbid conditions, which increases the likelihood of polypharmacy and potentially harmful drug–drug interactions (DDIs). As antiretroviral (ARV) therapies evolve, the nature and frequency of these interactions also change, highlighting the need for continued vigilance.MethodsWe conducted a retrospective cohort study at the University Hospital of Liège (Belgium). We collected and analysed antiretroviral drugs (ARVs), comedications, and demographic and clinical data from 2017 to 2022. We used the University of Liverpool HIV drug interaction database to identify contraindicated red-flag interactions.ResultsWe observed a significant and continuous increase in the use of non-ARV medications in our cohort. Drug-drug interactions (DDIs) remained common and usually involved a boosted ARV regimen. The number of red-flag DDIs decreased over time after 2017 for several reasons including switching to unboosted ARV regimens. Topical steroids and proton pump inhibitors were the drugs most frequently involved in contraindicated DDIs among the comedications.ConclusionPolypharmacy in people living with HIV (PWH) is a growing concern. Although the level of contraindicated drug-drug interactions (DDIs) has decreased over time, it remains a significant issue. Active monitoring and the implementation of alert systems can help clinicians mitigate the risk of such interactions.